THE POLICY OF LEGAL PROTECTION FOR FEMALE PRISONERS IN CLASS II A FEMALE CORRECTIONAL INSTITUTIONS IN SEMARANG - Martinus Aditya Pardiyanto (Universitas 17 Agustus 1945 Semarang, 2022)
Women convicts, as a vulnerable group in society, are a group that must receive guaranteed protection for their human rights. The problem in this research is the legal protection of female prisoners in the Class II A Women’s Prison in Semarang, the problems faced, and the efforts made to overcome the problems in providing legal protection to female prisoners. The approach method used is juridical-normative. This research is descriptive-analytical. The types of data used are secondary data and primary data. Data collection methods include library research, interviews, and documentation studies, and are then analyzed descriptively and qualitatively. Based on the study’s results, it can be seen that legal protection for female prisoners in the Class II A Women’s Prison in Semarang is carried out by fulfilling all the rights of female prisoners as stipulated in the legislation. In principle, all the rights of women prisoners have been granted and fulfilled, although they are still limited and not yet at the maximum level. Problems faced by the Semarang Women’s Class II A Prison in providing legal protection to female prisoners, including: (1) the limitations of existing human resources, both in quantity and quality; (2) over capacity; (3) the condition of the prison building is not following the minimum standard; (4) the lack of health facilities provided; (5) the lack of information and communication systems; and (6) minimal operating budget. Efforts made by the Class II A Women’s Prison in Semarang to overcome these problems, such as (1) increasing the quantity and quality of prison officers either through proposals for adding new employees, partnership cooperation, or through correctional technical training; (2) proposing new women’s prisons in the area of Central Java province and simplifying procedures for fulfilling the rights of inmates such as assimilation, CMB and PB consistently and transparently; (3) the renovation of prison buildings adapted to the concepts and ideas of correctional that leads to the fulfillment of the rights of women prisoners; (4). improving the health facilities and facilities for the residents of prisons; (5) procurement of information technology-based correctional service facilities and infrastructure; (6) implementing a budget system based on the real needs of the correctional process and the fulfillment of special unit costs. This study concludes that the legal protection of female prisoners in the Class II A Women’s Prison in Semarang follows what is mandated in the legislation.